Bullying Experiment based on The Doers’ Perspective, Victim and Eye Witness on The Junior High School Student - Masruroh, Nurlailatul (University of Muhammadiyah Malang, 2016)
The Bullying Phenomena of 40 countries showed that Indonesia is ranked as the world's second highest state for bullying cases. The aim of this study is to provide an overview of Bullying Experience in Perspective Actors, Victims and Witnesses of The Junior Student